(untitled) (International Journal of Engineering and Computer Science, 2018)
The goal of this propose design is to detect drowsiness in drivers to prevent accidents and to improve safety on the highways. A method for detecting driver drowsiness/sleepiness is developed on Arduino microcontroller board based on Atmega328P for real-time monitoring. The readings taken from different sensors used in this project can be seen in an Android based mobile device. It has an MQ-2 alcohol gas sensor to detect alcohol, if consumed by the driver and a relay circuit to stop him from performing the drive if alcohol consumed. The output from the relay activates the GSM module which sends a message to the driver family. MPU-6050 Micro-Electro-Mechanical-System (MEMS) accelerometer to read the head nodding conditions combined with a gyroscope and a temperature sensor to know the temperature inside the vehicle. The system is also able to monitor the driver physiological conditions such as heart pulse rate, eye blink detection using pulse sensor and eye blink sensor respectively. The alarm will be activated when the driver has consumed alcohol or driver head nods frequently or heart pulse rate goes above the limit or when driver eyes get closed. The microcontroller communicates with the android mobile through HC-05 Bluetooth module connected on the board. The android mobile is provided with the facility to view continuous readings from the sensors connected to the system along with the warning status messages through an android software based application installed in the end device.